Behavioural Approaches in Neuropsychological Rehabilitation - Wilson, Barbara A. (Neuropsychological Rehabilitation: A Modular Handbook, 2003)
The potential of behavioural approaches for improving the lives of people with acquired brain injury is immense. Here that potential is laid out and explored with a thoroughgoing regard for clinical practice and the theoretical frameworks that underpin that practice. This book will prove an invaluable resource for clinical psychologists and the whole range of therapists working with patients suffering from acquired brain damage.